Mitochondria promote septin assembly into cages that entrap Shigella for autophagy - Krokowski, Sina (Autophagy, 2017)
Septins are cytoskeletal proteins implicated in cytokinesis and host-pathogen interactions. During macroautophagy/autophagy of Shigella flexneri, septins assemble into cage-like structures to entrap actin-polymerizing bacteria and restrict their dissemination. How septins assemble to entrap bacteria is not fully known. We discovered that mitochondria support septin cage assembly to promote autophagy of Shigella. Consistent with roles for the cytoskeleton in mitochondrial dynamics, we showed that DNM1L/DRP1 (dynamin 1 like) can interact with septins to enhance mitochondrial fission. Remarkably, Shigella fragment mitochondria and escape from septin cage entrapment in order to avoid autophagy. These results uncover a close relationship between mitochondria and septin assembly, and identify a new role for mitochondria in bacterial autophagy.